(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The nature of a person’s communicative activity depends on his communicative ability, communicative values ​​recognized by him, specific characteristics of motivation and communication needs. Thus, communicative competence is a holistic, relatively stable, integrated psychological formation that is manifested in individual psychological, personal characteristics in the behavior and communication of a certain person. Despite the difference in the understanding of the components of communicative competence, all authors agree that, in fact, communicative competence is the ability to establish and maintain necessary relationships with other people.